Ammonia nitrogen adsorption by different aquifer media: An experimental trial for nitrogen removal from groundwater. Issue 9 (20th October 2020) - Li, Duo; Zhou, Yahong; Long, Qi; Li, Rui; Lu, Changyu
Abstract: Groundwater resources in North China are scarce, and nitrogen pollution, especially ammonia nitrogen pollution, in groundwater is a severe environmental challenge for this area. In this context, the effects of differentaquifer media on ammonia nitrogen adsorption in Hutuo river plain, north China were investigated in the study. In particular, the aim of this study was to investigate the influence of Eh, clay particle and organic material content on ammonia nitrogen adsorption. The study found that Eh affected the migration and transformation of NH4 + -N in aquifer media. When the clay particle content was less than or equal to 14%, the NH4 + -N adsorption reached the equilibrium state in 210 min. The adsorption was the maximum when the clay content was 14% in the study. The NH4 + -N adsorption of by three sand types increased with the increase of clay content. Meanwhile, the concentration of NO2 − -N and NO3 − -N increased, though the change was not significant. The increase in the organic matter content enhanced the oxidation of the medium, and pH value continued to decline, leading to H + and NH4 + forming a competitive relationship in the solution. However, the NH4 + -N adsorption capacity gradually increased as the organic matter consisting of more cation adsorption sites.